Experiences and expectations regarding COVID-19 prevention and control measures among the hill tribe population of northern Thailand: a qualitative study - Siwarak Kitchanapaibul; Anusorn Udplong; Tawatchai Apidechkul; Ratipark Tamornpark; Thanatchaporn Mulikaburt; Peeradone Srichan; Soontaree Suratana; Fatima Yeemard; Pilasinee Wongnuch (BMC Public Health, 2021)
Abstract Background COVID-19 has been a major human threat for a year. A large number of people have been infected and killed globally, including hill tribe people living in remote and border areas between Thailand and Myanmar. Different expectations of and experiences with the implemented disease prevention and control measures by local, national and international organizations have been widely reported. This study aimed to understand the experiences and expectations regarding the disease prevention and control measures that were implemented among hill tribe people in Thailand. Methods Qualitative data were collected from participants aged 20 and older who belonged to the hill tribes living on the border of northern Thailand and Myanmar. A semistructured questionnaire was used to guide interviews. Information was extracted for thematic analysis by the NVivo program. Results Fifty-seven participants (36 female, 21 male) were interviewed; 27 participants were Thai Yai, 14 participants were Yunnan Chinese, 8 participants were Akha, and 8 participants were from other tribes. The average age was 45.8 years (min = 20 years, max = 90 years). Thirty participants had never attended school, and the other 27 participants had received education at different levels, from primary school to higher education. Forty participants were unemployed, 13 worked as agriculturists, and the other 4 were attending school. Both positive experiences, such as improving personal hygiene practices, maintaining close contact and increasing relationships among family members and demonstrating the leadership of the villager leaders, and negative experiences, including interruption of social interactions, family financial problems, poor access to medical care services, and invisible people to the government, were found. Different expectations were observed regarding organizations at the local, national, and international levels. Expectations at the local level included villagers and community leaders taking action to strongly contribute to prevention and control measures and to prevent unscreened people from entering the village. Obtaining accurate information about the disease and being financially supported were expectations at the national level, while closing borders to protect cases from overflowing into their villages was an international-level expectation. Conclusion Although hill tribes reside in very remote rural areas, they experience both positive and negative effects of the disease prevention and control measures implemented by organizations. Their expectations are formally and informally voiced to policy makers at the local, national and international levels.